INCULCATE CRITICAL THINKING SKILLS IN PRIMARY SCHOOLS - Prameswari, Salvina Wahyu; Suharno, Suharno; Sarwanto, Sarwanto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This paper aims to describe the inculcation of critical thinking skills in primary schools. Critical thinking is a complex thinking process that is thinking in a reflective, independent manner and aims to make reasonable decisions, which include analyzing, synthesizing, recognizing problems and solving them, concluding and evaluating. Critical thinking skills in primary school is still not maximal because the teacher still has not triggered the students to think critically. This research uses descriptive qualitative method with literature study data collection techniques. Based on literature review, it can be concluded that critical thinking skills is a high-level thinking process that needs to be instilled since students in elementary school.